Benefício de prestação continuada: reflexos da precarização do trabalho e (des)proteção previdenciária - Polonio, Isangela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The presented dissertation analyzes the profile of the applicants of the Continuous Cash Benefit Program (BPC) for person with disabilities and their implications for the world of work and social security conditions in the city of Paranaíba/MS. The construction of the study come at first, the reflection on the work as a form of capitalist production of accumulation and its organization, culminating in social protection systems. Given the theme of social protection based in the wage citizenship of the advanced countries which is not consolidated in the peripheral systems - gives the construction of the Brazilian Social Security under the influence of social security and its consolidation as a constitutional guarantee, considering the binomial: logic securitarian and social logic. Time when the Social Assistance acquires status of law, and toward marks the no-contribution, disassociated from work category. The nonsense is established when neoliberal policies marked the context of its regulation and implementation, with a system aimed at selectivity, targeting and privatization. Thus, within this policy it establishes the Continuous Cash Benefit Program - object of this study, constitutionally recognized in 1988 as the provision of a social minimum, for a person with disabilities and elderly with a guaranteed minimum wage, which does not have own conditions or family members to fill those posts. The approach of this reality is experienced in this study, given the uniqueness of the city of Parnaíba (MS), chosen as the basis for empirical research framework. 494 Individual User Registers were analyzed of the Social INSS Service User (CIU / SS), from 2009 - 2013. In order to understand how precarious labor relations and social security protection interfere with social protection, we found that 77% of the applicants have already played remunerated activities, among these 62% in informal labor relations; and, of all the applicants, about 71%...

Esta dissertação analisa o perfil dos requerentes do Benefício de Prestação Continuada (BPC) para pessoa com deficiência e as implicações do mundo do trabalho e das relações previdenciárias no município de Paranaíba (MS). A construção do estudo percorre, a reflexão sobre o trabalho como forma de produção capitalista de acumulação e sua organização, que culmina nos sistemas de proteção social. Diante da temática da proteção social pautada na cidadania salarial dos países avançados - o que não se consolidou nos sistemas periféricos - dá-se a construção da Seguridade Social brasileira sob a influência do seguro social e sua consolidação como garantia constitucional, considerando o binômio: lógica securitária e lógica social. Momento em que a Assistência Social adquire status de direito, e em sua direção imprime a não contributividade, desassociada do trabalho. O contrassenso se estabelece quando diretivas neoliberais marcaram o contexto de sua regulamentação e implementação, com medidas voltadas para seletividade, focalização e privatização. Neste contexto se configura o Benefício de Prestação Continuada - objeto deste estudo, constitucionalmente reconhecido em 1988, como a provisão de um mínimo social, destinado a pessoas com deficiência e idosas que não possuam condições próprias ou de familiares para seu provimento, com a garantia de um salário mínimo mensal. A aproximação dessa realidade é vivenciada neste estudo, dada a singularidade do município de Paranaíba (MS), escolhido como base para o referencial empírico da pesquisa. Foram analisados 494 Cadastros Individuais do Usuário do Serviço Social do INSS (CIU/SS), no período de 2009 - 2013. Para compreender como as relações precárias de trabalho e de proteção previdenciária interferem na proteção social, identificamos que 77% dos requentes já desempenharam atividade...
Keywords: Serviço social; Benefício de prestação continuada - Brasil; Previdência social - Mato Grosso do Sul; Trabalho - Aspectos sociais; Assistência social; Direitos sociais; Seguridade social - Brasil; Social service